Isolation, identification & pathogenicity test of causal agent of dieback-like symptom of plumeria spp. - Anuar, Norshahadib (2016)
Plumeria spp. is an ornamental tree in the family Apocynaceae that can grow up to 9m tall and it is natively found in tropical America. The strong scent of their flowers is the main attraction in the landscape area. However, this ornamental tree can be infected by several diseases such as the stem rot, black tip rot, leave rusts and dieback. Based on some related reports, dieback may be caused by fungus from Botryosphaeriaceae family. In Malaysia, there is no report found about the causal agent of dieback on Plumeria spp. even though the symptom has been observed and less case reported in other countries. In this research, the objectives were 1) to identify the causal agent of dieback on Plumeria spp and 2) to conduct pathogenicity test to verify the causal agent. The infected samples were collected from landscape area in Tropicana Height in Kajang, Selangor on May 2016 to July 2017. The pathogen was isolated and cultured on Potato Dextrose Agar (PDA) medium. The causal agent of dieback on Plumeria spp. was confirmed by Koch’s Postulate method using 15 healthy stem cuttings of Plumeria spp at 4-6 weeks old by re-isolating the pathogen in PDA media. For objective 1, the fungal pathogen was identified through morphological and molecular characteristics. From morphological analysis, the fungus was grayish to black in color and turned out to be dimorphic in culture. The conidia were ellipsoid, translucent and mix with paraphyses ranging from 3.5-5 x 6.5-12 μm in size and arranged in arthric chains. Meanwhile, for molecular analysis the culture samples were successfully extracted and amplified by PCR using ITS1 and ITS4 primers to produce about 1000 basepairs (bp). The PCR products were sent for sequencing and identified by using Basic Local Alignment Tool (BLAST). From BLAST analysis, it has about 971 nucleotide sequences for ITS1. The ITS1 gene has 99% of identity and 95% of the query covered for the sequence. Based on morphological characteristics and ITS sequence region, the pathogen was identified as Neoscytalidium dimidiatum. For objective 2, pathogenicity test was successfully done and shows that both plant species of P. rubra and P. obtusa shows the same severity when inoculated with this pathogen in duration of two weeks. It can be concluded that this fungus is the main pathogen that cause dieback-like symptom on this plant species. Generally, this is the first report of dieback disease on Plumeria spp. caused by Neoscytalidium dimidiatum in Malaysia.